2011
DOI: 10.3892/mmr.2011.529
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression profiles of the Hedgehog signaling pathway between microsatellite-stable and microsatellite-unstable colorectal cancers

Abstract: Abstract. The present study aimed to investigate the expression of the Hedgehog (Hh) signaling pathway between microsatellite-unstable (MSI) and microsatellite-unstable (MSS) colorectal cancers (CRCs). A total of 61 samples of CRC tissue and corresponding blood samples were obtained from the surgical department of our hospital. The tissue samples were examined by immunohistochemistry using antibodies against Sonic Hh (SHH), Pathed (PTCH) and Gli1, and evaluated independently for protein expression by two patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(22 reference statements)
2
4
0
Order By: Relevance
“…In the present study, no correlation was found between Shh immunoexpression and most clinicopathological features. In one study, there were similar findings [ 24 ]. In other studies, there were some different results.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In the present study, no correlation was found between Shh immunoexpression and most clinicopathological features. In one study, there were similar findings [ 24 ]. In other studies, there were some different results.…”
Section: Discussionsupporting
confidence: 61%
“…Also they reported that well differentiated tumours shown more intense Shh expression than high grade carcinomas [ 1 ]. Others found that there was no association between Shh and tumour differentiation [ 2 24 ]. During embryogenesis, the Hh signalling pathway is essential for organ patterning, cell differentiation and cell proliferation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, Gli1 expression level in CRC tissues varies from 30% to 79%, with staining being either cytoplasmic or nuclear (46)(47)(48)(49)(50)(51). In our study, 45,87% of the tumors stained positive for Gli-1.…”
Section: Discussionsupporting
confidence: 56%
“…Patched-1 overexpression has been correlated with moderately differentiated tumors (47) and nodal status (50), as well as, with worse DFS and OS in patients with earlystage cancer that underwent curative treatment (47,50). Contradictory results were reported in a small study of 19 patients, where low levels of Patched-1 mRNA expression were associated with a higher risk of metastasis (54).…”
Section: Discussionmentioning
confidence: 98%
“…The study by Stefanius et al revealed no correlation between Hh and colorectal serrated adenocarcinomas 59. Hu et al also reported that Hh signals were more frequently expressed in the microsatellite instable group, compared with the microsatellite stable group in CRC 60. All those studies described that the activation of the Hh signaling pathway is restricted in several types of CRC, but not in other types of cancer.…”
Section: Hh Signaling Pathway In Crcmentioning
confidence: 98%